Dynamics of Vagal Activity Due to Surgery and Subsequent Rehabilitation - Grote, Vincent; Levnajić, Zoran; Puff, Henry; Ohland, Tanja; Goswami, Nandu; Frühwirth, Matthias; Moser, Maximilian (Frontiers in Neuroscience, 2019)
Background Vagal activity is critical for maintaining key body functions, including the stability of inflammatory control. Its weakening, such as in the aftermatch of a surgery, leaves the body vulnerable to diverse inflammatory conditions, including sepsis. Methods Vagal activity can be measured by the cardiorespiratory interaction known as respiratory sinus arrythmia or high-frequency heart-rate variability (HRV). We examined the vagal dynamics before, during and after an orthopedic surgery. 39 patients had their HRV measured around the period of operation and during subsequent rehabilitation. Measurements were done during 24h circadian cycle on ten specific days. For each patient, the circadian vagal tone was calculated from HRV data. Results Our results confirm the deteriorating effect of surgery on vagal tone. Patients with stronger pre-operative vagal tone suffer greater vagal withdrawal during the peri-operative phase, but benefit from stronger improvements during post-operative period, especially during the night. Rehabilitation seems not only to efficiently restore the vagal tone to pre-operative level, but in some cases to actually improve it. Discussion Our findings indicate that orthopedic rehabilitation has the potential to strengthen the vagal activity and hence boost inflammatory control. We conclude that providing a patient with a vagal reinforcemnet procedure prior to the surgery (“pre-habilitation”) might be a beneficial strategy against post-operative complications. The study also shows the clinical usefulness of quantifying the cardiorespiratory interactions.